The Federation of South African Women and the Black Sash : constraining and contestatory discourses about women in politics, 1954-1958 - Sturman, Kathryn (Department of Political Studies, 2016)
The period 1954 to 1958 saw an unprecedented level of mobilisation and active political campaigning by women of all races in South Africa. These campaigns were split along lines of race and class, as evidenced in the demonstrations against the extension of pass laws to African women by the Federation of South African Women [FSAW] and the campaign against the Senate Bill by liberal white women of the Black Sash. What they had in common is that both groups of women organised their action into separate structures exclusive to women, with independent identities from the male-dominated structures of the Congress Alliance and of white party politics. This separate organisation from men was not carried out with an explicit feminist agenda or a developed awareness of women's oppression, however. Nevertheless, their existence constituted a challenge to the dominant patriarchal discourse that constructed women's role as domestic and exclusive to the private sphere. Newspaper representations of the two organisations by both their political allies and their political opponents, provide evidence of this dominant discourse on "women's place" and insight on the public perception of political activity by women at the time. Within the texts of FSAW and the Black Sash one finds tensions between accepted notions of women's primary role as wives and mothers, and an emerging self-conception of women as politically active in the public realm. To an extent, the self-representation of these texts mirrors the patriarchal representations of women found in the newspaper reports. However, there are also definite departures from the traditional formulations of womanhood that can be conceived of as "contestations" to the dominant discourse. The patriarchal discourse was, therefore, a discursive constraint, both external and internalised, on women's ability to become active and effective in South Africa politics in the 1950s. Paradoxically, through the practical process of women's mobilisation in FSAW and the Black Sash, new space was opened on the political terrain that allowed for the alteration of the dominent discourse on women's place in society, as well as for the emergence of contestatory feminist discourses in South Africa.